2022
DOI: 10.21533/epiphany.v15i1.393
|View full text |Cite
|
Sign up to set email alerts
|

Female Academics’ Role in Peace-Building, State-Building and Gender Equality in Bosnia and Herzegovina

Abstract: Twenty-seven years after the end of the war, Bosnia and Herzegovina (BiH) is still considered a post-conflict state dealing with war memories, genocide, socio-political divisions, and political and socio-economic challenges like ethno-nationalism, unemployment, social inequalities, a complex education system, high levels of corruption, migration, and depopulation. The article aims to investigate the role of female academics in peace-building, state-building and gender equality in Bosnia and Herzegovina. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…However, support and trust from colleagues are among the motivational factors that give strength to women leaders to hold leadership roles. Jelešković & Mulalić (2022) revealed that the support of colleagues, especially women, towards female leaders produces positive changes that female leaders will bring. Therefore, colleagues in the department or faculty need to give full support to women leaders so that every planned initiative yields results that will be shared together.…”
Section: (Ii)mentioning
confidence: 99%
“…However, support and trust from colleagues are among the motivational factors that give strength to women leaders to hold leadership roles. Jelešković & Mulalić (2022) revealed that the support of colleagues, especially women, towards female leaders produces positive changes that female leaders will bring. Therefore, colleagues in the department or faculty need to give full support to women leaders so that every planned initiative yields results that will be shared together.…”
Section: (Ii)mentioning
confidence: 99%